Refining Japanese Pronunciation through Digital Innovation: Tools and Strategies Based on Phonetic Theory - Najoan, Franky Reymond; Piri, Elvie Nitje (Vocational College of Diponegoro University, 2026)
This study aims to identify the level of awareness, usage, and perceptions of digital tools for Japanese pronunciation learning among teachers, students, and alumni in Indonesia, and to analyze the challenges associated with their integration in both classroom and self-directed learning. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews involving 122 participants from diverse educational backgrounds and Japanese learning experiences. The findings show that while 58.2% of respondents are aware of digital tools for Japanese learning, only a small portion are familiar with pronunciation-specific tools. Quizlet, NHK Pronunciation, and OJAD were the most frequently mentioned, yet around 40% reported no awareness of any pronunciation-focused applications. Major obstacles identified include limited access to devices or stable internet (26%), lack of teacher guidance (16%), and usability difficulties (12%). Despite infrequent use, 94% of respondents perceived digital pronunciation tools as helpful, particularly those that provide native speaker voice samples and pitch or intonation visualization. These insights highlight the importance of leveraging phonetic theory—particularly in relation to pitch-accent perception and auditory-visual feedback—to refine pronunciation instruction through technology. Overall, the study underscores the need for improved teacher training, stronger classroom integration, and the development of more accessible and user-friendly pronunciation tools tailored to Indonesian learners’ needs.